ANALISA CAMPURAN BETON POROS DENGAN UKURAN AGREGAT KASAR 9.5 - 19 MM DAN PENAMBAHAN POLYAMIDE FIBER - Willy Susanto; Abdi Septia Putra; Alrend Roy Peterson Kaputing (Racic : Rab Construction Research, 2024)
The issues of climate crisis and sustainability have garnered significant attention in the 21st century, driven by the industrial revolution and the burgeoning human population. This has resulted in various environmental challenges, including energy crises, global warming, and the scarcity of water resources. Sustainable cities must consider economic, infrastructural, social, and environmental aspects. One of the environmental challenges in urban development is the availability of water in the future. Vertical drainage utilizing pervious concrete technology is regarded as a solution to address this issue. Pervious concrete contains voids that enhance water absorption.This study aims to optimize the compressive strength, tensile strength, and permeability of pervious concrete through the addition of polyamide fibers. The findings indicate that the addition of 1.25% fibers enhances the tensile strength of concrete, albeit at the expense of compressive strength. Specimens with and without fibers exhibit better permeability capabilities than planned, indicating increased voids and permeability in coarse aggregates sized 9.5-19 mm.